Identificación y análisis de factores de éxito en la gerencia de proyectos con equipos virtuales en el sector de Tecnologías de la Información (TI) (2017)
The research work proposes the identification and analysis of success factors of the management of projects that include virtual teams in the sector of Information Technology (IT). In order to contribute in the probability of success of project management with virtual teams in the IT sector, through identify the most common success factors in the environment and thus be able to implement them in the different projects from the beginning of these.